Organization in Government Management in Development in Tirta Buana Village, Dapurang District - Marhana, Marhana; Nurlina, Nurlina; Syamsu, Suhardiman; Hidayat, Ihsan (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The aim of this research is to examine the organization of government management in development in Tirta Buana village, Dapurang district. This research uses a qualitative approach. Research location in Tirta Buana village, Dapurang District, Pasangkayu Regency. The informants in this research were 5 officials at the Tirta Buana Village Office, Dapurang District. The results of the research show that the organizational aspect of community development in Tirta Buana Village has not gone very well, this can be seen from the organizational weakness which lies in the human resources of the government apparatus, namely, in this case the village head gives responsibility to the section head to manage development planning. fully. However, this responsibility is not in accordance with the competencies possessed, so that the division of work in implementing development has not run optimally.